Study on Corrosion Behaviour of n-Type Porous Silicon Layer in Tetramethylammonium Hydroxide Solution - Xiang, Zhen; Lai, Chuan (Asian Journal of Chemistry, 2014)
The corrosion behaviour of n-type porous silicon layer in tetramethylammonium hydroxide solution with or without ethanol was studied by weight loss measurements. The results show that the corrosion rate goes up with increasing temperature and decreases with increasing the volume ratio of ethanol in 0.5 M tetramethylammonium hydroxide. The activation parameters of Ea, A, DHa and DSa for n-type porous silicon layer corrosion in 0.5 M tetramethylammonium hydroxide were calculated and discussed.